Towards a Harm-Minimising Approach to Sex Work: A Call for Decriminalisation in England and Wales - LANG, VICTORIA,CAROLINE,VILVEN (2015)
This thesis has developed a harm-minimising framework to analyse the regulation of sex work in England and Wales and propose a system of reform. In so doing, it defines the ‘harm’ in sex work as that of stigma, violence and exploitation, using this categorisation to judge the effectiveness of any (new) system of legal regulation. This thesis demonstrates how sex workers are frequently cast as a deviant population and separated from the rest of society, facing extreme forms of violence and exploitation. Using my harm-framework of analysis, this thesis examines the regulation of sex work in England and Wales, starting with the Contagious Disease Acts of the 1860’s through to modern day. In doing this, it will demonstrate the ability of the law to maintain, shape and create the conditions for the violence, exploitation and stigma faced by women selling sex. The thesis then explores alternative means of regulating sex work. It will look towards the alternatives of criminalising the clients, regimes of legalisation and of decriminalisation. It concludes that in order to provide the sex worker with sufficient protections against violence, stigma and exploitation, England and Wales should adopt a regime of decriminalisation. It is only under such a regime that sex workers could be provided with effective and realistic safeguards against the harm currently endemic in their work, and within which, crucial steps can be made towards altering their stigmatised and marginalised status